Canton Kung Fu: The Culture of Guangdong Martial Arts. (July 2019) - Ye, Guo
During the 20th century, a version of Kung Fu from the Guangdong region in Southern China became more widely known abroad as a result of Chinese migration to the West, as well as its exposure through popular culture, including the films of Bruce Lee. This article analyses the culture of Guangdong martial arts in the context of this growing exposure. A variety of martial arts sects and associated cultural expressions in other fields give a picture of the traditional martial arts culture in Guangdong. Underpinning these physical manifestations, Guangdong martial arts have derived their ideologies from traditional Chinese philosophy. The dynamic social system supporting Guangdong martial arts provided a platform ensuring that these cultural symbols and values could be created and maintained and exported over several centuries.